1970
DOI: 10.1177/030098587000700609
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral Infection in Suckling Arabian Foals

Abstract: This preliminary report describes an adenoviral infection recently recognized in Arabian foals. Clinically, the condition is suggestive of pneumonia and is frequently progressive and fatal. This article refers to 10 cases that had similar histories and postmortem lesions. The presence of large amphophilic intranuclear inclusions in respiratory epithelia of all cases suggested a viral etiology and prompted the current investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…All foals also had typical lesions of adenovirus infection [5] and hypoplasia of all lymphoid organs as has been described [ 61.…”
Section: Resultsmentioning
confidence: 63%
“…All foals also had typical lesions of adenovirus infection [5] and hypoplasia of all lymphoid organs as has been described [ 61.…”
Section: Resultsmentioning
confidence: 63%
“…The first equine SCID cases were reported in 5 to 8-monthsold 29 Arabian foals, had limited resistance to infections (10). Later, similar immunodeficiency syndromes were also described by several researchers in Arabian horses from different geographic regions (6,9,23). Studies indicated that the immunodeficiency observed in these foals was caused by lymphopenia, hypogammaglobulinaemia, the failure of germinal centers to form in lymphoid organs (7,10,12,13,25).…”
Section: Introductionmentioning
confidence: 82%
“…Most of the affected foals with severe immunodeficiency generally die before they reached to their six months of ages. Thus, SCID is one of the most frequent causes of Arabian foal deaths, which are unresponsive to the antimicrobial treatment (1,4,8,9,19). It also means that, even though all-infectious etiologies lying under the clinical course are treated, SCID maintains tremendous immunodeficiency in those foals.…”
Section: Introductionmentioning
confidence: 99%
“…Affected foals usually develop bronchopneumonia and occasionally conjunctival infection and panuveitis, although the latter is seldom clinically evident (McChesney et al 1973). Affected foals usually develop bronchopneumonia and occasionally conjunctival infection and panuveitis, although the latter is seldom clinically evident (McChesney et al 1973).…”
Section: Local/metastatic Spread Of Diseasementioning
confidence: 99%